Ambiguous presentation of Mycobacterium avium complex‐associated Rasmussen aneurysm. Issue 3 (23rd February 2017) - Chiu, Hsin‐Wei; Kuo, Shu‐Hung; Lai, Ruay‐Sheng; Wu, Ming‐Ting; Wu, Hsiu‐Fu
Abstract : A 77‐year‐old man with a progressively dry cough (two months duration) was admitted with hemoptysis. Chest computed tomography (CT) revealed left lingular lobe consolidation and one thick‐walled cavity lesion over the left lower lobe, which was accompanied by satellite micro‐nodules in a tree‐in‐bud pattern. CT‐guided biopsy confirmed mycobacterial infection, and subsequent culture yielded Mycobacterium avium complex (MAC). Unremitting hemoptysis was present despite treatment (14 days) with ethambutol, rifampin, clarithromycin, and streptomycin. Initial CT angiography (CTA) to determine the source of the hemoptysis revealed a suspected aneurysm in the consolidated left lingular lobe; however, this could not be localized via catheter angiography during the pulmonary and bronchial arterial phases. Two weeks later, a massive hemoptysis episode led to haemodynamic instability and serious consequences. Follow‐up CTA confirmed the previously detected aneurysm, and glue embolization was performed successfully. This case report highlights a rare but catastrophic MAC‐associated pseudoaneurysm and relevant treatment options. Abstract : This case report highlights a rare but catastrophic MAC‐associated pseudoaneurysm and relevant treatment options.